Strategy for the Development of Islamic Education Institutions in the Academic Sectors - Machfudz, Machfudz; Zaini, Mohammad (Letiges, 2023)
Realising the development of educational institutions that will produce competitive graduates, have good morals and impact increasing the quality of Islamic education that can compete and be competitive with other educational institutions by trying to focus on handling institutional management so that it is better by focusing on development in the academic sector. This study aims to identify and analyse institutional development strategies in the academic sector at MA Mambaul Ulum Jember. Qualitative research by looking at the problems and research objectives to be achieved. This research uses a type of phenomenological research. Data collection techniques include interviews, observation and documentation. Data analysis by condensing data, presenting data and drawing conclusions/verification. The results of his research: Institutional development in the academic field is carried out by changing views on education, complying with Ministry of National Education policies, creating a good institutional culture, and changing the learning process. The institutional development strategy in the Academic Sector at MA Mambaul Ulum Jember is implemented by adjusting: The strategy for developing Islamic education institutions at MA Mambaul Ulum Jember is implemented by: 1) Forming students' competitive mindset through rewards, 2) Developing teacher creativity in the teaching and learning process, 3) Innovation in learning services, 4) curriculum innovation. In implementing education, the quality of academic services must be carried out in a directed, disciplined manner and guarantees the realisation of good quality education.